PERLINDUNGAN HUKUM BAGI MASYARAKAT DALAM TRANSAKSI JUAL BELI GAS LPG 3 KILOGRAM MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Faizal Idris, Reza; Sulistiyantoro, Heru (Universitas Maritim AMNI Semarang, 2022)
To meet the needs of life, there is a relationship between business actors and consumers. The relationship between business actors and consumers is interdependence. To protect the interests of consumers, the Consumer Protection Act is urgently needed due to the weak position of consumers towards business actors. The purpose of this study was to determine the form of legal protection for consumers in obtaining 3 kilograms of LPG (Liquified Petroleum Gas) at a price according to the HET (Highest Retail Price). The research method used in this study was a normative juridical research method with data collection through library research and interviews in order to collect and study library materials or secondary data. The result of the research is that regulations regarding consumer legal protection and consumer disputes in Indonesia have been regulated in Law Number 8 of 1999 concerning Consumer Protection. In addition, socialization is needed from the government and related institutions regarding the rights of 3 kg lpg consumers, such as the right to obtain information about the price of 3 kg lpg, information about the availability of 3 kg lpg gas at bases and so on, especially in the city of Surabaya.